Melatonin interaction with abscisic acid in the regulation of abiotic stress in Solanaceae family plants - Ali, Muhammad; Pan, Yupeng; Liu, Hanqiang; Cheng, Zhihui (Frontiers in Plant Science, 2023)
Solanaceous vegetable crops are cultivated and consumed worldwide. However, they often confront diverse abiotic stresses that significantly impair their growth, yield, and overall quality. This review delves into melatonin and abscisic acid (ABA) biosynthesis and their roles in abiotic stress responses. It closely examines the intricate interplay between melatonin and ABA in managing stress within plants, revealing both collaborative and antagonistic effects and elucidating the underlying molecular mechanisms. Melatonin and ABA mutually influence each other’s synthesis, metabolism and that of other plant hormones, a key focus of this study. The study highlights melatonin’s role in aiding stress management through ABA-dependent pathways and key genes in the melatonin-ABA interaction. Specifically, melatonin downregulates ABA synthesis genes and upregulates catabolism genes, leading to reduced ABA levels. It also directly scavenges H2O2, enhancing antioxidant enzyme activities, thereby underscoring their collaborative role in mediating stress responses. Moreover, the interplay between melatonin and ABA plays an essential role in multiple physiological processes of plants, including stomatal behaviors, wax accumulation, delay leaf senescence, seed germination, and seedlings growth, among others. Recognizing these relationships in Solanaceae vegetable crops holds great importance for improving agricultural practices and crop quality. In summary, this review offers a comprehensive overview of recent studies on the melatonin and ABA interplay, serving as a valuable resource for researchers and breeders dedicated to fortifying crop resilience and productivity within challenging environments.